A study on knowledge and practice of breastfeeding in the field study area of a medical college in Haldia, West Bengal, India - Majumder, Ronjoy; Samsuzzaman, M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Breast milk contains all the nutrients an infant needs in the first six months of life. After 6 months of exclusive breastfeeding (EBF), WHO recommends infants should receive complementary foods. Only less than half of infants in India initiate breastfeeding within an hour and just about half are exclusively breastfed until 6 months. We conducted this study on various knowledge and practices for successful exclusive breast feeding. Methods: A cross sectional study was conducted with pretested and prestructured questionnaire on mothers of children in age group of 6 moths to 5 years. Results: Only 18 (21.7%) are working, 10 (12%) are illiterate and 7 (8.4%) are graduate. All of the mothers have heard about EBF. Mothers with correct knowledge of colostrums feeding being beneficial for baby (0.006), prelacteal feeding being harmful to baby (0.0003), knowledge of continuing EBF when baby is sick (0.00002), education (0.00015), when to start complementary feeding(0.001), institutional delivery (0.00002), when latching explained by nurses (0.0116), those who practiced burping (0.017), were significant for EBF for 6 months. Only 42 (50.6%) of mothers fed colostrum to their babies. Conclusions: In this study it was seen that mothers with knowledge for different aspects of breast feeding had more chance of successful EBF. Female literacy was found out to be a strong indicator for successful EBF and also a indicator for colostrum feeding in future pregnancy. Special attention to be given to raise awareness of family members, specially mother in law so that complementary feeding can be started at 6 months.